2018
DOI: 10.1111/bju.14462
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction rate at 1‐year follow‐up in patients treated with penile implants: data from the multicentre prospective registry INSISTED

Abstract: This study reports high functional and patient satisfaction scores at 1 year after PPI surgery using a dedicated tool for the first time. Better outcomes should be expected for patients treated by surgeons with greater experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…However, a prospective cohort study that included 142 Italian subjects has not found a significant association between Peyronie's disease and dissatisfaction (in such study, the only variable associated with satisfaction was the surgeon's experience). 38 Although a variety of studies show the subject's psychological characteristics associated with dissatisfaction with the penile prosthesis implantation, 13,39 the literature on how the preoperative psychological evaluation should be performed is scarce. The present evaluation protocol uses standardized tools and open interviews with an in-depth investigation of multiple realms of the patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prospective cohort study that included 142 Italian subjects has not found a significant association between Peyronie's disease and dissatisfaction (in such study, the only variable associated with satisfaction was the surgeon's experience). 38 Although a variety of studies show the subject's psychological characteristics associated with dissatisfaction with the penile prosthesis implantation, 13,39 the literature on how the preoperative psychological evaluation should be performed is scarce. The present evaluation protocol uses standardized tools and open interviews with an in-depth investigation of multiple realms of the patient's life.…”
Section: Discussionmentioning
confidence: 99%
“…This data can be explained by the intensive pre- and postoperative counseling that every patient received, which allowed us to provide the patient with realistic expectations about the IPP implantation, to instruct the patient to a correct use of the device and to promptly detect and manage postoperative technical issues [ 15 , 16 ]. Furthermore, as many authors suggest, being all surgical procedures performed by the same surgeon with a wide experience in penile implantation, we think that surgeon's experience could be a predictor of satisfaction in this kind of surgery [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study reported high patient satisfaction scores after 1 year of penile implant surgery, especially if the patients were treated by surgeons with higher level of experience (Capogrosso et al, ).…”
Section: Discussionmentioning
confidence: 99%